KEPENTINGAN INDONESIA BEKERJA SAMA DALAM BIDANG PERTAHANAN DENGAN UKRAINA - Andrew Elkharist Ginting; Umi O. Retnaningsih (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The effect of the arms embargo imposed by the US on Indonesia has reduced the deterrence of the Indonesian military force and coupled with the old defense equipment, it is not commensurate with the area that must be guarded. Therefore, Indonesia needs cooperation partners to increase its military strength and to modernize defense equipment. Ukraine was chosen as a cooperation partner in the defense sector because the defense equipment offered is in accordance with Indonesia's geography and is free of embargoes. This research will examine what interests Indonesia wants to achieve through this cooperation. The theory used in this research is K.J Holsti International Cooperation Theory with the concept of national interest by Hans Morgenthau. The data used is secondary data from books, journals, mass media and internet websites. The research method uses library research by analyzing data from the sources listed. The results of this study indicate that Indonesia's interests in cooperation in the defense sector with Ukraine include economic interests by expanding the market to Eastern Europe, defense interests, and political interests. Through this cooperation, Indonesia's interests are achieved in fulfilling its defense capacity and capability to ward off unpredictable threats by purchasing combat vehicles from Ukraine to improve the quality of the TNI's defense equipment. Keywords: military, national interest, defense equipment, defense cooperation.